2015 IEEE Symposium on Service-Oriented System Engineering 2015
DOI: 10.1109/sose.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Automated Testing of Web Services Based on Algebraic Specifications

Abstract: The testing of web services must be done in a completely automated manner when it takes place on-thefly due to third-party services are dynamically composed to. We present an approach that uses algebraic specification to make this possible. Test data is generated from a formal specification and then used to construct and submit service requests. Test results are then extracted and checked against the specification. All these are done automatically, as required. We present ASSAT (Algebraic Specification-Based S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Another advantage of algebraic specification is that it enables automated testing of software against formal specifications [23], [24]. These test automation techniques can be applied to the implementation of system security design formally specified in algebraic specifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another advantage of algebraic specification is that it enables automated testing of software against formal specifications [23], [24]. These test automation techniques can be applied to the implementation of system security design formally specified in algebraic specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Algebraic specification is a formal method that supports specification refinement, verification and software testing. It has been widely used in the formal development of objectoriented software, software components and Web services [23]- [25]. Our empirical studies [26]- [28] demonstrated that algebraic specifications are easy to learn and to understand.…”
Section: Algebraic Specificationmentioning
confidence: 90%
See 1 more Smart Citation
“…Other recent work with the same goal of testing cloud services from abstract specifications includes an automated approach that generates useful tests from algebraic specifications but does not especially address test‐coverage issues and a high‐level method for specifying different kinds of robustness tests for a cloud platform, based on input validation, or state‐space exploration, or concurrent access stress‐testing , which does not address full test automation.…”
Section: Comparison With Related Workmentioning
confidence: 99%
“…Algebraic specifications are at a very high level of abstraction, independent of any implementation details, and can be used directly in automated software testing [10]- [12]. However, algebraic specifications do not directly support efficient searching of services, and neither do other formal methods.…”
Section: Introductionmentioning
confidence: 99%